Physical and Sensory Perturbations Changed Joint Regulations in Control of Posture: A Power Spectral Analysis - Mohammed Ashtiani (Shiraz University of Medical Sciences, 2021)
Background: Standing on an unstable platform needs more effort from neuromusculoskeletalsystem. This study was about to highlight the joint regulationsin keeping balance, while standing on an unstable platform using spectralanalysis.Methods: Thirteen healthy young males were participated in this cross-sectionalstudy to stand on an unstable platform with two levels of support stiffness, twovisual, and three cognitive dual-task conditions. Motion analysis was utilizedto measure postural regulations at the lower extremity joints. Power spectralanalysis was applied on the joint rotations to discriminate the joint behaviors indifferent standing conditions.Results: Results showed that the body used higher levels of postural adjustmentby more joint regulations as the standing conditions became more difficult.Support stiffness of the platform and vision were effective in keeping balance(p <0.05), while the dual cognitive tasks had no significant effect (P>0.05). Insimpler standing conditions, the ankle-hip strategy was responsible for bodystabilization in lower frequencies. However, increasing the standing difficultyby eliminating the vision or use of looser support of the platform was led to thepredominance of ankle strategy.Conclusion: Standing in different conditions prevailingly relied on the anklestrategy. The enhancement of postural difficulty may revert to dominantly usethe ankle strategy.